Multifocal Necrotizing Leukoencephalopathy: Expanding the Clinicopathologic Spectrum. Issue 4 (7th February 2019) - Premji, Sarah; Kang, Loveleen; Rojiani, Mumtaz V; Kresak, Jesse; Rojiani, Amyn M
Abstract: Multifocal necrotizing leukoencephalopathy (MNL) is a rare condition typically described in patients undergoing chemotherapy or with HIV/AIDS. As a pathologic entity, it is characterized by multiple small foci of necrosis typically within white matter of the pons and occasionally in other areas. Herein we describe findings in 6 patients with MNL, 5 diagnosed at postmortem examination and 1 by surgical biopsy. Histopathologic features were characteristic, with generally small foci of necrosis, most frequently within the pontine base, although larger lesions were seen in the frontal white matter and basal ganglia. Axonal swellings, occasional dystrophic calcification and minimal microglial activity or reactive responses were common. Glial fibrillary acidic protein immunoreactivity was absent or markedly reduced within the lesions although it remained well defined in the surrounding areas. The underlying clinical circumstances ranged from HIV/AIDS, hematologic malignancy, chemotherapy for malignancies to postcardiac transplant, the latter reported for the first time. A significant common thread identified in our cases was altered immune status. A second common factor, which has also been previously implicated, was the presence of significant ongoing infection or sepsis. The role of concurrent inflammatory processes, specifically proinflammatory cytokine release in the context of these complex clinical scenarios is discussed with possible pathogenetic considerations.